Cervical spine fractures and rear car seat restraints. Issue 12 (December 1987) - Conry, B G; Hall, C M
Abstract : Two cases of potentially fatal cervical spine fractures in children who were inadequately restrained by malfunctioning car seat restraints are presented. Adequate parental maintenance of seat restraints and their readjustment when children change from wearing lightweight to thick, heavy clothing are imperative.